The Microsoft ® Data Warehouse Toolkit: With SQL Server 2008 R2 and the Microsoft ® Business Intelligence Toolset, Second Edition - Mundy, Joy (John Wiley & Sons, 2012)
In this book, leading data warehouse experts from the Kimball Group share best practices for using the upcoming “Business Intelligence release” of SQL Server, referred to as SQL Server 2008 R2.